Completing your EdD : the essential guide to the Doctor of Education - Burnell, Iona; Roffey-Barentsen, Jodi (Emerald Publishing Limited, 2020)
This is an essential text for students pursuing the Doctor of Education programme (EdD). Written by EdD teachers and course leaders, it covers essential elements of the EdD including reading and writing at doctoral level, planning and executing research, and much more, and will accompany students as they successfully progress through their EdD.